PREVALENCE AND RISK FACTORS OF GESTATIONAL DIABETES MELLITUS (GDM) IN PREGNANT WOMEN: A CROSS-SECTIONAL STUDY. - Bukke, soujanya; Begum, Anisa; Dubbudu, Poojitha (Student's Journal of Health Research Africa, 2025)
Background: Gestational Diabetes Mellitus (GDM) is a growing public health concern with significant implications for both maternal and fetal health. Identifying its prevalence and associated risk factors is essential for timely diagnosis and preventive interventions. Methods: A cross-sectional study was conducted among 500 pregnant women attending antenatal clinics at a tertiary care hospital between January 2023 and May 2024. GDM was diagnosed using the 75-gram oral glucose tolerance test (OGTT) following the World Health Organization (WHO) criteria. Data on maternal age, body mass index (BMI), family history of diabetes, previous obstetric history, and lifestyle habits were collected through structured interviews and clinical records. Results: The prevalence of GDM in the study population was 16.8% (n = 84). A statistically significant association was observed between GDM and maternal age ≥30 years (p < 0.01), pre-pregnancy BMI ≥25 kg/m² (p = 0.002), family history of type 2 diabetes mellitus (p < 0.001), previous history of GDM (p < 0.01), and sedentary lifestyle (p = 0.03). Among women diagnosed with GDM, 61.9% were aged ≥30 years, and 70.2% had a BMI ≥25. Multivariate logistic regression analysis identified advanced maternal age (adjusted odds ratio [AOR] = 2.4; 95% CI: 1.4–4.1) and family history of diabetes (AOR = 3.1; 95% CI: 1.8–5.4) as the most significant independent predictors of GDM. Conclusion: This study highlights a considerable prevalence of GDM and identifies advanced maternal age, higher BMI, and positive family history as key risk factors. Targeted screening and early lifestyle interventions, particularly for high-risk groups, are crucial to minimizing maternal and fetal complications associated with GDM. Recommendations: Early GDM screening, targeted counseling, antenatal lifestyle interventions, postpartum follow-up, health education, and integration of GDM care into maternal health policies are essential to improve maternal and fetal outcomes.